Transition‐Metal‐Free Deaminative Vinylation of Alkylamines. Issue 21 (10th September 2019) - Hu, Jiefeng; Cheng, Bo; Yang, Xianyu; Loh, Teck‐Peng
Abstract: The amino group is one of the most fundamental structural motifs in natural products and synthetic chemicals. However, amines potential as effective alkylating agents in organic synthesis is still problematic. A unified strategy has been established for deaminative vinylation of the alkylamines with vinyl boronic acids by C−N bond activation under catalyst‐free conditions. The key to the high reactivity is the utilization of pyridinium salt‐activated alkylamines, with a base as a promoter. The transformation exhibits good functional group compatibility, and includes inexpensive primary amine feedstocks and amino acids. The proposed method can serve as a powerful synthetic method for late‐stage modification of complex compounds. Mechanistic experiments suggest that free radical processes are involved in this system. Abstract :